Electrophysiology of motor pathways for sphincter control in multiple sclerosis. - Mathers, S E (1990)
The central and peripheral motor pathways serving striated sphincter muscle function were studied using cortical and lumbar transcutaneous electrical stimulation, pudendal nerve stimulation and sphincter electromyography in 23 patients with multiple sclerosis (MS), and sphincter disturbance, including incontinence of urine or faeces, urinary voiding dysfunction, or constipation. The central motor conduction time was significantly increased in the MS group compared to controls (p less than 0.05). Damage to both the upper and lower motor neuron pathways can contribute to sphincter disturbance in MS. The latter may be due to coexisting pathology or to involvement of the conus medullaris by MS.